(untitled) (World Bulletin of Management and Law, 2025)
The article examines the current issue of implementing artificial intelligence (AI) in legislative processes, both in international practice and within the context of the Republic of Uzbekistan. Examples of the application of artificial intelligence in the legislative activities of various countries are analyzed, and its advantages - increasing the effectiveness, transparency, and scientific validity of rule-making - are highlighted. At the same time, potential risks, including issues of algorithmic bias and data confidentiality, are addressed. Special attention is paid to the steps being taken in Uzbekistan to create a regulatory and institutional framework for the implementation of AI in the public administration system, including the legislative sphere. It is concluded that the implementation of AI as a strategic tool for the digital transformation of legislative activity is necessary.